DEPARTMENT OF THE GENERAL PEDAGOGY AND PEDAGOGY OF HIGHER SCHOOL IN THE STRUCTURE OF THE H.S. SKOVORODA KHARKIV NATIONAL PEDAGOGICAL UNIVERSITY : PAGES OF THE HISTORY - Золотухіна, С.; Зеленська, Л. (New Collegium, 2020)
Based on the analysis of the pedagogical literature and archival sources, we have discovered the origins of the Pedagogical Department within the Pedagogical institution of the Kharkiv imperial University, its genesis in the structure of the H.S. Skovoroda Kharkiv National Pedagogical University. We have defined the peculiarities of functioning of the department as a structural unit of the H.S. Skovoroda Kharkiv National Pedagogical University, characterized the activities of its members and heads.